2015
DOI: 10.1007/s11356-015-5187-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PCB126 and PCB153 on telomerase activity and telomere length in undifferentiated and differentiated HL-60 cells

Abstract: PCBs are persistent organic pollutants with carcinogenic, immune- and developmental toxicity. This suggests that they may interfere with normal cell maturation. Cancer and stem/progenitor cells have telomerase activity to maintain and protect the chromosome ends, but lose this activity during differentiation. We hypothesized that PCBs interfere with telomerase activity and the telomere complex thereby disturbing cell differentiation and stem/progenitor cell function. HL-60 cells are cancer cells that can diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro , immortalized human skin keratinocytes, hamster lung fibroblasts, immortalized lymphocytes, or human promyelocytic leukemia cells exposed to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ), have shortened telomeres (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Conversely, PCB 138 and PCB 153 upregulate c- myc in vitro (Ghosh et al, 2007; Gribaldo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition PCB126 (dioxin-like) and PCB153 (non-dioxin-like) reduced telomerase activity in HL-60 cells and shortened telomeres after 30 days of exposure (Xin et al 2016). Our finding that blood plasma of PCB-exposed individuals inhibits telomerase expression in lymphoproliferation assays is well in line with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating telomere dynamics in PCB-exposed individuals or PCB-treated telomerase positive tumor cell lines have been published (Xin et al 2016; Jacobus et al 2008; Shin et al 2010; Senthilkumar et al 2011, 2012; Mitro et al 2015). Whereas in two population-based studies low dose exposure to non-ortho PCBs was associated with longer TL in leukocytes (Shin et al 2010; Mitro et al 2015), long-term treatment of cell lines with PCBs resulted in cell-type and PCB congener-specific adverse effects on TL, htert activity and expression of telomere-associated shelterin genes (Xin et al 2016; Jacobus et al 2008; Senthilkumar et al 2011, 2012). Based on these recent findings, we selectively analyzed TL of granulocytes and lymphocytes in peripheral blood from individuals occupationally exposed to very high levels of PCBs.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere attrition and telomerase dysfunction, which are reported to be involved in stem cell dysfunction (failure to self-renew and differentiate) (Zhang and Ju 2010) and immune function injury (Eisenberg 2011), can also be induced by PCBs in HaCaT cells (Jacobus et al 2008;Senthilkumar et al 2011;Senthilkumar et al 2012) and HL-60 cells (Xin et al 2015). However, no study so far has investigated if PCB126 affects telomeres and telomerase of stem cells and impacts their differentiation capacity.…”
Section: Introductionmentioning
confidence: 99%